Percutaneous lung biopsy: should it be avoided or not? - Cezar I. BETIANU; Andrei V. NEAGU; Daniel PANTILE; Ana D. PASCARIU; Alexandru BAJENARU; Andreea I. NEAGU; Giorgiana ION; Andrei BONDARI (Archives of the Balkan Medical Union, 2020)
Introduction. Percutaneous core biopsy (PCB) is a minimally invasive, widely available and relatively safe procedure enabling pathological diagnosis in oncological patients.